2018
DOI: 10.1111/jerd.12443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen peroxide on color and whiteness of resin‐based composites

Abstract: Objective: To evaluate the influence of a 35% hydrogen peroxide gel on color and whiteness changes of resin-based composites (RBC).Materials and Methods: Discs (n = 10; shade A3.5 enamel; and 8 mm diameter and 2 mm thick) were fabricated from three RBC (DF-Durafill, Heraeus Kulzer; ED-IPS Empress Direct, Ivoclar Vivadent; and AP-Amelogen Plus, Ultradent Products). Three subgroups were obtained for each RBC: before bleaching (T 0 ) and after first (T 1 ) and second (T 2 ) bleaching applications. A dental spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 44 publications
5
40
1
2
Order By: Relevance
“…These results may be attributed to the different whitening mechanisms according to the different contents and longer total contact time of WP. In agreement with this result, previous studies showed that total bleaching time is more important than the concentration of the bleaching agent. The increase in contact time may cause more HP diffusion into the resin matrix leading to more hydrolysis of chemical bonds between the resin matrix and fillers, which may result in the removal of fillers.…”
Section: Discussionmentioning
confidence: 99%
“…These results may be attributed to the different whitening mechanisms according to the different contents and longer total contact time of WP. In agreement with this result, previous studies showed that total bleaching time is more important than the concentration of the bleaching agent. The increase in contact time may cause more HP diffusion into the resin matrix leading to more hydrolysis of chemical bonds between the resin matrix and fillers, which may result in the removal of fillers.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this approach is subjective and depends on visual perception and acuity, training and environment. Therefore, instrumental color determination (spectrophotometry) and the use of standardized formulas to calculate color difference should be preferred, enabling detection of minor differences, hardly perceived by the general observer ( 15 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Os géis clareadores mais utilizados para o método de branqueamento são compostos de peróxido de hidrogênio ou mesclados com outros componentes, a exemplo do peróxido de carbamida e o perborato de sódio (Parreiras, 2014). Segundo Pecho (2018), o agente clareador de escolha para uso profissional em consultório é o peróxido de hidrogênio a 35%, e na técnica caseira o peróxido de carbamida nas concentrações 22%, 16% e 10%.…”
Section: Revisão Da Literaturaunclassified
“…O mecanismo de ação envolvido no clareamento se dá, a partir de um processo de oxidação dos pigmentos cromóforo, onde ligações complexas são convertidas em ligações mais simples, resultando assim na conversão de material orgânico em dióxido de carbono e Research, Society and Development, v. 9, n. 11, e4299119934, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.9934 6 água (Pecho, 2018). Essa ação oxidante é desempenhada pelo peróxido de hidrogênio que, se difunde pelos espaços entre os sais inorgânicos do esmalte dentário, para quebrar as moléculas orgânicas de pigmento, determinando assim o efeito clareador (Alqahtani, 2014).…”
Section: Revisão Da Literaturaunclassified